If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(2x+3)-4=3(2x+5)
We move all terms to the left:
5(2x+3)-4-(3(2x+5))=0
We multiply parentheses
10x-(3(2x+5))+15-4=0
We calculate terms in parentheses: -(3(2x+5)), so:We add all the numbers together, and all the variables
3(2x+5)
We multiply parentheses
6x+15
Back to the equation:
-(6x+15)
10x-(6x+15)+11=0
We get rid of parentheses
10x-6x-15+11=0
We add all the numbers together, and all the variables
4x-4=0
We move all terms containing x to the left, all other terms to the right
4x=4
x=4/4
x=1
| x^2-3=34 | | -6n-2n=16n= | | -66=6(x | | 9n^2+2=578 | | x-3=-1→x=20 | | -h/4=-4 | | -3+1.2=-3y+15-18 | | 5s=490 | | -6=r/8 | | 1/2x+x=180−x | | 2a+73=-4a+19 | | x+7=-9→x=16 | | 3n-I=8 | | 8n^2+5=21 | | -13z+(-3z)=32 | | 12x+x=180−x | | 783=27g | | 2x-16+9x=72 | | –9−8b=–7b | | 19=-24(4+z)-3 | | 3=-w/5 | | 2x^2-3x-22=x^2-12 | | 4x+x=74 | | 4j=732 | | 6y+29=-5(y+3) | | 2x-5x+4=(-3x+4 | | -48=m12 | | 5+4c=9 | | 6x+2=7+2x+8x+7 | | -48=m12 | | 8n+15=55 | | -3(w-7)+2w=17 |